Parodia w opowiadaniach Tatiany Tołstoj - Kalita, Liliana (Studia Rossica Posnaniensia, 2015)
Tatyana Tolstaya is one of the most accomplished contemporary Russian writers. She represents a postmodernist trend of which parody is a vital part. In her prose one can find parodies of political systems, social groups, romantic ideals, Soviet reality and human behavior. The article analyzes Tolstaya’s use of parody in her most popular stories, i.e. Hunting the Wooly Mammoth, Fire and Dust, Night, The Fakir and Okkervil River.